Evaluation of the floaterm concept at marine container terminals via simulation - Dulebenets, M. A.; Golias, Mihalis; Mishra, Sabyasachee; Heaslet, W. C. (My University, 2015)
International seaborne trade rose significantly during the past decades. This created the need to increase capacity of existing marine container terminals to meet the growing demand. The major objective of this paper is to evaluate the floaterm concept using simulation modeling and determine if it can improve terminal productivity. The main difference between floaterm and conventional marine container terminals is that, in the former case, transshipment containers are handled by off-shore quay cranes and stored on container barges. Two terminal configurations performance is compared (vessel handling times and equipment utilization) under normal and disruptive conditions. Computational experiments confirm preliminary expectations that the floaterm concept can enhance efficiency of marine container terminal operations under normal and disruptive conditions.
Keywords: Maritime transportation; Container terminals; Simulation; Floating quay cranes